ANALYSIS OF THE CONTRIBUTION AND INTERACTION BETWEEN INFLATION, ZAKAT POTENTIAL AND POVERTY LEVEL TOWARDS THE HUMAN DEVELOPMENT INDEX (HDI) - Muhammad Syahwali; Arbanur Rasyid; Rukiah (RADJA PUBLIKA, 2025)
The Human Development Index (IPM) is an illustration of the development of human welfare in a country. Indonesia, which has 34 provinces and several provinces still have HDI levels, some are still below 70% and are in the moderate HDI category. This condition can be related to policies taken from a country both from the strategy of maintaining inflation, empowering zakat potential and maintaining poverty levels. The purpose of this study was to analyze the influence, interaction and causality relationship between inflation, zakat potential, poverty level and human development index in provinces in Indonesia. The theory used in this study is related to macro variables such as inflation, zakat potential, poverty level and the Human Development Index. This research is a quantitative study using secondary data with a sampling technique with saturated sampling of 34 samples, and analyzed using the VAR method with computer program statistical toolsEviews 10. The research results show based on analysisVector Error Correction Model(VECM) Inflation has an effect of 27%, the potential for zakat has an effect of 0.002%, and the poverty rate has an influence of 10.4% Based on the analysisImpuls Response Function (IRF), The potential for zakat is the variable that has the highest response by other variables, then the response to the poverty rate and finally the inflation variable where the dynamic shock is stable between the 15th to the 20th year. Results of the analysisForcast error Variance Decomposition (FEVD) shows the potential for zakat and the poverty rate to be the variables that have the greatest contribution to other variables, namely 31.44% and 4,76%. The variable that has the lowest response and contribution to other variables is the inflation variable of 3.79% .